(3TQM RjL GHf jhfS GdeUQis - (3dGHf jhfS GdeUQjs; (3CHh GdMSf Ydj Hf CHj SYjO GdefLe,J (B399 (3g` s
(3ChdgG (B:s
(3HYO GdHSedg (B: (3GdaUd GdKGfi ai MQcGJ GdchGcH heG jdjb Cf jPcQ eYgG s
(3BNQgG (B:s
(3hMaXfG eG MUd ef cd hGMO efgG hGdMeO ddg hMOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B68 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B965s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjg (B((3ejbGJ (B1106) s
Keywords: (3Gdadcs